Study of Antisense DNA Oligomer Targeting of Histone Deacetylase 1 (HDAC1) mRNA for Potential Knockdown Effects and Therapeutic Implications - Kim, Seung Chan (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Histone Deacetylase (HDAC) is an enzyme that eliminates the acetyl group from the histone octamer complex. The acetylation state of histone proteins is a major interest in epigenetic gene expression. HDAC1 is closely related to various cell responses including the progress of the cell cycle, proliferation and gene expression. HDAC1 inhibitors are used for anticancer therapeutics by controlling multiple signaling protein kinases like SAPK, ERK and TNF-alpha. Here, we used single-strand DNA 18-oligomer to mimic RNA interference technology. The study modeled the HDAC1 mRNA secondary structure and identified the possible four siRNA binding sites by higher possibility than the miR-449 targeting site. Also, its possible configuration is being modeled according to binding energies. Three frames, where the possibility of siRNA binding is low, were randomly identified as positive controls. HDAC1 full mRNA sequence was identified and its starting open reading frame was also identified. Here, 10 secondary structures of HDAC1 mRNA were generated according to total bond energy and binding energies. As a result, the 18-omer single-strand DNA was generated according to the identified sequences. In this study, this preliminary data can be further warranted to generate HDAC1 knockdown activity and its comparison to the current HDAC1 inhibitors. The generation of single-strand DNA as an antisense sequence to a specific mRNA can be utilized for therapeutics along with RNAi. With the thermodynamically stable structure of DNA compared to RNA, it can be applied for long-term usage. mRNA targeting needs additional toxicological testing in order to construct clinical trials.